Innovative Development of Kazakhstan’s Raw Material (Oil and Gas) Regions: Multifactorial Model for Empirical Analysis - Kurmanov, Nurlan; Beisengaliyev, Yerzhan; Bayandin, Marat; Syzdykova, Elmira; Tolysbayeva, Madina (International Journal of Energy Economics and Policy, 2022)
The following paper reveals the applied aspects of multi-factor analysis allowing identifying patterns of innovative development of Kazakhstan’s raw material (oil and gas) regions in connection with modernization transformations. Initial signs of indicators for the period between 2008 and 2020 are currently under investigation using factor analysis. All data have been analyzed with IBM SPSS 23. In considerable detail, authors describe the methodology of this study and provide the results of statistical analysis. The analysis has revealed factors determining implementation of modernization transformations and taking effect on innovative development of Kazakhstan’s raw material regions, which are as follows: Regional Economic Development and Agglomeration Effects, Market Potential and Infrastructure, Structural Factor of Innovative Development, Human Factor of Innovative Development, and Investment Factor of Innovative Development. It is concluded that stimulation of innovation activity can be based on the following public policy measures: increasing investment in fixed assets; growth of gross regional product and product and process innovation costs; regional development of information and communication technologies; expansion of lifelong learning programs; poverty reduction; increase in the share of R&D employees; development of small businesses; increasing investment in education and in the number of technical and STEM students. The obtained results also allowed us to conclude about the completeness of identified factors of innovative development of Kazakhstan’s raw material (oil and gas) regions and the need for further research in the context of studying the stated issue.